2020
DOI: 10.1038/s41467-020-19920-5
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-blockade uncovers stromal plasticity in tumors by revealing the existence of a subset of interferon-licensed fibroblasts

Abstract: Despite the increasing interest in targeting stromal elements of the tumor microenvironment, we still face tremendous challenges in developing adequate therapeutics to modify the tumor stromal landscape. A major obstacle to this is our poor understanding of the phenotypic and functional heterogeneity of stromal cells in tumors. Herein, we perform an unbiased interrogation of tumor mesenchymal cells, delineating the co-existence of distinct subsets of cancer-associated fibroblasts (CAFs) in the microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 100 publications
2
147
0
Order By: Relevance
“…Of these factors, TGF-β appears to be particularly important. Cancer-secreted TGF-β is capable of inducing CAF phenotype [ 111 , 112 , 113 ], and TGF-β signalling in CAFs is closely linked to poor clinical outcome [ 94 , 114 ], with inhibition leading to remodelling of CAF dynamics, better immune response, and disease regression in in vitro models. The well-established link between TG2 and TGF-β is therefore critical, with TGF-β upregulating TG2, while TG2 is also known to be capable of transforming inactive TGF-β to its active form [ 115 , 116 , 117 ].…”
Section: Tg2 As a Key Functional Player In The Tmementioning
confidence: 99%
“…Of these factors, TGF-β appears to be particularly important. Cancer-secreted TGF-β is capable of inducing CAF phenotype [ 111 , 112 , 113 ], and TGF-β signalling in CAFs is closely linked to poor clinical outcome [ 94 , 114 ], with inhibition leading to remodelling of CAF dynamics, better immune response, and disease regression in in vitro models. The well-established link between TG2 and TGF-β is therefore critical, with TGF-β upregulating TG2, while TG2 is also known to be capable of transforming inactive TGF-β to its active form [ 115 , 116 , 117 ].…”
Section: Tg2 As a Key Functional Player In The Tmementioning
confidence: 99%
“…Indeed, FAP High CAF-S1 are able to attract, retain, increase the survival of CD4+ CD25+ T lymphocytes and promote their differentiation into regulatory T cells (Treg) [ 133 , 134 , 154 ]. In line with the identification of several subsets among FAP High CAF-S1, recent data has demonstrated that only specific ones, characterized by ECM accumulation, wound-healing signature and TGFβ-signaling, are associated with an immunosuppressive tumor environment [ 139 , 141 , 142 , 155 ]. In particular, ecm-myCAF and TGFβ-myCAF cellular clusters are correlated with the content in FOXP3 + T lymphocytes in breast cancer, and are able to increase PD-1 and CTLA-4 protein levels at the surface of FOXP3 high Tregs [ 142 ].…”
Section: Cancer-associated Fibroblasts (Caf) Identity Function Anmentioning
confidence: 99%
“…Interestingly, accumulation of ecm-myCAF, wound-myCAF and TGFβ-myCAF clusters is correlated with resistance to immunotherapy in melanoma and non-small cell lung cancer patients [ 142 ]. Moreover, TGFβ inhibition has been shown to reduce myofibroblast features, while increasing immunomodulatories properties in murine carcinomas, thereby providing the rationale of combining TGFβ and PD-1/PD-L1 in clinical settings [ 155 ]. All these data shed light on CAF heterogeneity within tumors, in particular on the FAP High CAF-S1 subset, and demonstrate their different functions in tumor progression, metastatic spread, immunosuppression and resistance to immunotherapies.…”
Section: Cancer-associated Fibroblasts (Caf) Identity Function Anmentioning
confidence: 99%
“…In the tumor microenvironment, stromal cells are an abundant source of TGFβ [ 78 ], with cancer-associated fibroblasts (CAFs) the most significant producers [ 79 , 80 ]. Activated TGFβ signaling leads to CAF activation, CAF-mediated cancer progression [ 81 ] and may differently influence CAF subsets [ 82 ].…”
Section: Tgfβ Biology and Signaling In Cancermentioning
confidence: 99%
“…Noteworthy, CAF-derived TGFβ may contribute to immunosurveillance and escape and may participate in therapy resistance, including immunotherapy with immune checkpoint blockade [ 83 , 84 , 85 ], also by excluding CD8+ T lymphocytes from the tumor site [ 86 , 87 ]. A recent paper suggests that TGFβ neutralization targets only selected CAF subtypes and, in turn, promotes CAF immunomodulatory properties and the formation of an immune-permissive tumor microenvironment (TME) by regulating ECM density [ 82 ].…”
Section: Tgfβ Biology and Signaling In Cancermentioning
confidence: 99%